1999
DOI: 10.1177/000486589903200205
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Recent Innovations in New Zealand's Criminal Justice System: Empowering Maori or Biculturalising the State?

Abstract: T hiS paper provides an overview of the relationship between Maori and the criminal justice system in New Zealand since Moana jackson published "Maori and the Criminal justice System: He Whaipaanga Hou" in 1988. jackson argued that the cultural insensitivity and blas inherent in the criminal justice system, lies at the heart of the Maori over-representation problem. The focus of my paper is on the incorporation of Maori justice practices and philosophies within the family group conferencing forurn established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 8 publications
1
44
0
Order By: Relevance
“…Consistent with the ideology of biculturalism becoming the new orthodoxy in New Zealand (see Poata-Smith, 1997;Rata, 2003;Webster 1998) there was a shift toward theorising the overrepresentation of Maori in the criminal justice sector as being the result of historical and systemic cultural domination (see Maxwell & Morris, 1999;McFarlane-Nathan, 1999;Pratt, 1999;Tauri, 1999). In large part this was the legacy of Moana Jackson's (1987Jackson's ( , 1988 seminal work on the topic.…”
Section: The Nature Of Maori Offending: From Race To Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the ideology of biculturalism becoming the new orthodoxy in New Zealand (see Poata-Smith, 1997;Rata, 2003;Webster 1998) there was a shift toward theorising the overrepresentation of Maori in the criminal justice sector as being the result of historical and systemic cultural domination (see Maxwell & Morris, 1999;McFarlane-Nathan, 1999;Pratt, 1999;Tauri, 1999). In large part this was the legacy of Moana Jackson's (1987Jackson's ( , 1988 seminal work on the topic.…”
Section: The Nature Of Maori Offending: From Race To Ethnicitymentioning
confidence: 99%
“…Tauri describes the conclusion Jackson drew from his summary of the situation 'Therefore, for Maori to achieve justice they must have their own system, one that is not only based on tikanga Maori (values and practices) but also one that Maori themselves control ' (1999, p. 157). Although Tauri (1999) goes on to say that the official reaction to Jackson's report was largely dismissive, he also observes that on the basis of Jackson's work the government indicated that they were open to compromise.…”
Section: Postmodern Social Policy: From Class To Culturementioning
confidence: 99%
“…These types of community crime prevention programmes incorporated features of Māori responses to social harm, but became state-controlled and designed initiatives with "added" Māori cultural elements to existing intervention logic. 41 Even Puao te Ata Tu failed to escape. As recommended by Puao te Ata Tu, and agreed to be the earlier Labour government, a Social Welfare Commission and District Executive Committees were set up in 1990, with Māori representation on each.…”
Section: Māori and Neoliberalismmentioning
confidence: 99%
“…Thirdly, government-led RJ practices may result in additional harm. Tauri (1999) offers examples showing that New Zealand's FGC model for government-led RJ "fails to confirm that it empowers its Indigenous population" (p. 159). Strang and Sherman (2015) also exemplify harm by RJ especially for Aboriginal people in Australia: "The [RJ] experiment tells us that more victims were harmed, and offenders descended further and faster into crime when RJ conferences were used with [Aboriginal people] instead of prosecution in court" (Strang & Sherman, 2015, p. 10).…”
Section: Decolonization and The Criminal Justice Systemmentioning
confidence: 99%